2017
DOI: 10.1177/0748233717695431
|View full text |Cite
|
Sign up to set email alerts
|

Association between SNPs at IL-17A and IL-17F and susceptibility to accelerated silicosis

Abstract: The association between single nucleotide polymorphisms (SNPs) in the interleukin (IL)-17 gene and silicosis has been evaluated in different populations. The aim of the present study was to analyze the association between SNPs at IL-17A (-832A/G) and IL-17F (+7488A/G) and susceptibility to accelerated silicosis in the Iranian Kurdish population. We studied 48 patients with accelerated silicosis and 62 controls. Genomic DNA was isolated using the "salting out" method. PCR-RFLP was performed for all SNPs typing.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
0
3
0
2
Order By: Relevance
“…In our study, it was shown that serum 8-OHdG levels increased approximately 3 times in the exposure group and 2 times in the silicosis group compared with the control group. Hassani et al 44 demonstrated the importance of IL-17 in the development of lung fibrosis secondary to silica exposure. Recently, studies have shown that the IL-23/IL-17 axis has a significant impact on lung inflammation and pulmonary fibrosis 45 .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, it was shown that serum 8-OHdG levels increased approximately 3 times in the exposure group and 2 times in the silicosis group compared with the control group. Hassani et al 44 demonstrated the importance of IL-17 in the development of lung fibrosis secondary to silica exposure. Recently, studies have shown that the IL-23/IL-17 axis has a significant impact on lung inflammation and pulmonary fibrosis 45 .…”
Section: Discussionmentioning
confidence: 99%
“…All had died by the end of the 3-year follow-up. 56 Thirty-two men screened in a small agate mill in Guangzhou, China, found 15 cases of accelerated silicosis (prevalence of 47%) 27 3 ‡ 40-52 -2 (67%) Iran (2000-2007) 28 23 § 29 (13.7) 2 (0.6) 10 (43%) Italy (2004-2008) 29 1 ¶ 54 4 1 UK (2015) 30 6 ‡ 33.8 (5.9) 13 (5.3) 0 Iran (2017) 31 48 41 46 § 33 (29-37) 11 (9-17) 1 (2%) USA (2014) 42 1 ¶ 37 10 0 USA (1999-2003) 43 35 § --35 (100%) Italy (2015) 44 3 ‡ 48 (3.5) 13 (6) 0 Israel (2016) 45 47 19 § 47 (13.33) 11 (3.58) -Belgium (2018) 48 2 ‡ -<10 0 Australia (2018) 49 7 § 44 (26-61) 7 (4-10) 1 LTx (1%) Sandblaster Spain (2015) 50 1 ¶ 27 5 1 Czech Republic (2015) 51 1 ¶ 38 3.2 1 Turkey (2018) 52 1 ¶ 28 2 0 USA (2018) † † 53 101 § ---Stone crusher India (2015) 54 1 2 8 1 0 India (2015) 55 1 3 5 2 0 Jewellery and semi-precious stone workers India (2015) 56 19 -3.4 (1.7) 12 (63%) Brazil (2017) 57 57 32 12.5 6 (11%) China (2018) 34 15 (47% prevalence) 29 (4.9) 3.5 (1.7)…”
Section: Jewellery Polishersmentioning
confidence: 99%
“…Numerous infl ammatory cytokines contribute in every part of atherosclerosis (17)(18)(19)(20)(21)(22)(23)(24)(25). In this regard, the roles of chemoattractants including chemokine 2 (CCL2) and CCL5, which promote the recruitment of monocytes (18), as well as secretion of pro-infl ammatory cytokines: IL-1 β, IL-6, and TNF-α in NF-κB signaling in infl ammation (19) have been identifi ed.…”
Section: Introductionmentioning
confidence: 99%